A sensibilidade aos animais: uma análise de discurso - Alves Filho, Manoel Sebastião (Universidade Federal de São Carlos, 2025)
This research aims to analyze discourses on sensitivity toward animals produced within the contemporary domains of science, law, and non-governmental organizations, with the purpose of detecting, describing, and interpreting their specificities and differences in the constancy and intensity of affirmations and denials that animals are endowed with properties such as sensations, emotions, consciousness, and language. We seek to verify the hypothesis according to which sensations and emotions such as pain and distress are attributed to animals more regularly than cognitive or linguistic abilities. This research forms part of a broader problem concerning the understanding of a paradox of contemporary society: the excessive consumption of meat, the systematic slaughter of millions of animals, and the commercial success of agribusiness in a society that has become more sensitive toward animals. The study of the dictionary meanings of the word animal today constitutes the starting point for a historical survey of texts from Western civilization concerning animals. We depart from common discursive units, such as particular fields of knowledge, authors, works, and historical periods, in search of identifying more fundamental statements and discourses, whose force and scope enable them to exceed these fields, pass from one author to another, expand, and transcend the boundaries of time and space, of eras and places, thereby contributing to the constitution of today's complex conceptions of animality. Finally, we analyze contemporary texts from the three domains. Our theoretical premises and analytical procedures derive from Discourse Analysis as developed by Michel Pêcheux and enriched by the essential contributions of Michel Foucault. We also draw upon knowledge from two other relatively recent and original fields of historiography known as Animal History and the History of Sensibility. Our material comprises books, articles, interviews, declarations, judicial decisions, laws and bills, as well as texts published on websites and social media platforms, such as Instagram and Facebook.
Sensitivity toward animals: a discourse analysis.
Keywords: Análise de discurso; História dos animais; História das sensibilidades; Discourse Analysis; Animal History; History of Sensibility; LINGUISTICA, LETRAS E ARTES::LINGUISTICA::TEORIA E ANALISE LINGUISTICA; 10. Redução das Desigualdades; 15. Vida Terrestre